2012
DOI: 10.1155/2012/516718
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Matter of Life and Death—The Trials of Postnatal Beta-Cell Mass Regulation

Abstract: Pancreatic beta-cells, which secrete the hormone insulin, are the key arbiters of glucose homeostasis. Defective beta-cell numbers and/or function underlie essentially all major forms of diabetes and must be restored if diabetes is to be cured. Thus, the identification of the molecular regulators of beta-cell mass and a better understanding of the processes of beta-cell differentiation and proliferation may provide further insight for the development of new therapeutic targets for diabetes. This review will f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 277 publications
(303 reference statements)
1
32
0
1
Order By: Relevance
“…The balance in the pancreatic β-cells is pivotal in a right β-cell mass maintenance which would affect the function of β-cells. The β-cell mass is increased by neogenesis (differentiation from precursor cells), proliferation, and β-cell hypertrophy (increased cell size) and is decreased by β-cell death, primarily through apoptosis and β-cell atrophy (decreased cell size) (Tarabra et al 2012). A previous study has pointed out that the molecular mechanisms of CR delays the onset of age-related disease and extends life span in mammals, which may be associated with the alleviation of cellular apoptosis (Koubova and Guarente 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance in the pancreatic β-cells is pivotal in a right β-cell mass maintenance which would affect the function of β-cells. The β-cell mass is increased by neogenesis (differentiation from precursor cells), proliferation, and β-cell hypertrophy (increased cell size) and is decreased by β-cell death, primarily through apoptosis and β-cell atrophy (decreased cell size) (Tarabra et al 2012). A previous study has pointed out that the molecular mechanisms of CR delays the onset of age-related disease and extends life span in mammals, which may be associated with the alleviation of cellular apoptosis (Koubova and Guarente 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that age correlates with decreased proliferative activity and enhanced sensitivity to glucose-induced β-cell apoptosis (Maedler et al 2006). The β-cell proliferation was detected to gradually decline with aging by 0.5%~ 2% (Ackermann and Gannon 2007) and the imbalance between β-cell proliferation and apoptosis would finally result in β-cell dysfunction and consequently diabetes onset (Tarabra et al 2012). Therefore, seeking a feasible way to restore the β-cell mass and its functionality that decreased with increasing age would be quite important in delaying the onset of diabetes.…”
mentioning
confidence: 99%
“…Adult β cells have a low intrinsic replicative rate but retain some capacity for expansion in response to physiological perturbations such as pregnancy and obesity (3,4). A better understanding of molecular pathways that activate β-cell proliferation may help to define strategies for replacement of functional β-cell mass in both major forms of diabetes.…”
mentioning
confidence: 99%
“…Effect of OTUB2 on insulin secretion To determine whether knockdown of OTUB2 also affects insulin secretion, glucose-stimulated insulin secretion (GSIS) was examined in MIN6 cells and intact human islets, either untreated or treated with cytokines-conditions known to inhibit GSIS [1]. As shown in Fig.…”
Section: Effect Of Otub2 Sirnas On Viability Of Beta Cellsmentioning
confidence: 99%
“…Pancreatic beta cell dysfunction underlies essentially all major forms of diabetes [1]. In type 1 diabetes, cell death is caused by an autoimmune assault against beta cells by infiltrating lymphocytes resulting in autoimmune destruction, insulin deficiency and hyperglycaemia [2].…”
Section: Introductionmentioning
confidence: 99%